Madhusudana vagamr̥tam : outstanding achievements of Vidyavacaspati Madhusudana Ojha in the interpretation of Vedic thought in five volumes - Ramanathan, A. S.; Ojha, Madhusudan (ed.) (Jaipur Pt. Madhusudan Ojha Vedic Adhyayana Avam Shodh Peeth Sansthan, 2009)
Exhaustive study of the interpretation of Vedic literature, religion, philosophy and science; includes Sanskrit text also.
Keywords: Ojha, Madhusudana, 1866-1929 -- vedic literature -- history and criticism -- vedas and science -- Hindu philosophy